The Agsa System in the agrarian relations in selected barangays of Janiuay, Iloilo. - Montel, Jomer M
This study describes the dynamics of the agsa system and why it still persists after the implementation of Republic Act 6657 (June 1988), otherwise known as the Comprehensive Agrarian Reform Program. This law abolishes share tenancy effective on June 15, 1988., The study has three objectives. The first objective of the study is to find out patterns of landholding in Janiuay. Secondly, it aims to identify and describe the agsa system in Janiuay. Under this objective, the researcher establish points of comparison between agsa system and leasehold system. Lastly, the study aims to determine the reasons for the persistence of the agsa system in Janiuay. The locale of the study is in Januiay. There are four (4) barangays being studied: (1) Brgy. Jibolo, (2) Brgy. Danao, (3) Brgy. Tamuan I & II, (4) Brgy. Caraduan. These four barangays are selected based on the accessibility of the area and the fact that these barangays are where most of the share tenants are located (27 in Brgy. Jibolo; 10 in Brgy Danao; 32 in Brgy Tamuan I & II; and 22 in Brgy. Caraudan). Of the four barangays, twenty (20) tenants are purposively drawn as respondents. These 20 respondents are participating farmers of the Gintong Ani Program of the Department of Agriculture. Their tenurial status is share tenant. These 20 respondents are interviewed using the unstructured interview guide. There are different patterns of landholding existing in selected barangays of Januiay. These are the landownership, the CARP-regulated and the landless landholdings. Landownership, however, has two types, ranging from small landowners to big landlords. The agsa system in selected barangays of Janiuay in different variations. There is the 50-50 system or equal share of the total production between the landowner and the share tenant. All expenses are subtracted from the total production before division no matter who shoulders the expenses, whether it be the landowner or the share tenant. Secondly, there is the tresya system or the 2-1 share. Depending who shoulders the expenses, all expenses are subtracted or the cost of the binhi only subtracted from the total production before division. These are instances, however, where the share tenant shoulders all expenses but these expenses are not subtracted from the total production. Instead, they immediately divide it based on their 2-1 share. And lastly, there is the kwarta-parte system or the 3-1 share. In this system of payment, it is the share tenant who shoulders all the production expenses. Only the binhi is subtracted from the total production before division or there is none at all. Despite the abolition of share tenancy by RA 6657, share tenancy persists in selected barangays of Januiay. There are three factors that caused its persistence. Tradition is one of the reasons of persistence of agsa system in selected barangays of Janiuay. Agsa system has been practiced since they were born, consequently, they just follow it. Second, share tenants are powerless to demand tenurial arrangement due to the fact that they do not own the land they till. It belongs to somebody else. Last, since land is their only and primary source of living, share tenants would not dare to risk to lose the privilege of tilling it. Share tenancy in selected barangays of Januiay appears to be transforming into leasehold system. This is so because share tenants have already a Certificate of Land Transfer and sharing is 75-25 percent, as mandated by the CARP. The 25 percent, which is supposedly the payment for the land rent, it is given to the landlords as their share from the products produced by the land. This means that the essence of share tenancy, which is, obviously, sharing, remains despite its abolition through RA 6657. This kind of tenurial arrangement persists in selected barangays of Januiay because of lack of political will by political leaders to implement the law.